RAGAM METODE PENYULUHAN PEMBANGUNAN MELALUI PEMBERDAYAAN MASYARAKAT PELAKU AGRIBISNIS PADA POKLAHSAR BATUANG SRIKANDI NUSANTARA - Sultani; Ahmad Fachri (PT. Media Akademik Publisher, 2024)
Development in all sectors continues to be encouraged, including in the agribusiness sector. One of the efforts to develop the agribusiness sector is through development extension in community empowerment which aims to realize the independence of agribusiness actors. There are many types of development outreach methods, especially in community empowerment efforts. Mardikanto in his book entitled